IDENTIFIKASI SUMBER PENCEMAR DAN ANALISIS KUALITAS AIR TUKAD SABA PROVINSI BALI - Putu Desy Darmasusantini; I Nyoman Merit; I G.B Sila Dharma (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2015)
Availability of clean water for drinking water increasingly scarce, then efforts to utilize alternative flow of river water as drinking water and raw water industry one of them is Saba River. Purpose of research is to determine the characteristic of pollution source which will be impactto the changing of water quality in physical, chemical, and biological in up, middle and down stream area of Saba River, water quality and pollution index of Saba River. Determination of samples by using purposive sampling method. Sampels were taken at six points with repetitions three times at different times. Sampels taken at two points upstream, two points middle and two points downstream. Samples were analyzed in situ and ex situ. The results showed that the activities that affect water quality physical, chemical, and biological in up, middle and down stream area of Saba River is agricultural activities, livestock, restorant, blacksmith, home stay, residential, workshops, market, laundry and industrial activities. The upstream region until middle region (T1) no parameter exceeded the quality standard, parameters that exceed the quality standard in the middle region (T2) is TSS, BOD, fosfat and fecal coliform, in the downstream which exceeded the parameters in the downstream region (H1) is BOD, fosfat, fecal coliform dan total coliform and in the downstream region (H2) is DO, BOD, COD, fosfat, fecal coliform dan total coliform. Saba River quality status based on the method pollution index in the upstream region (U1) until middle region (T1) showed good condition, middle region (T2) until downstream pollutants classified as mild.